The Role of Islamic Religious Education Teachers in Developing Students’ Spiritual and Existential Intelligence - Siagian, Mhd. Rusli; Harahap, Muhammad Yunan (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The cultivation of spiritual and existential intelligence from elementary school age is a fundamental aspect in shaping a generation that is faithful, virtuous, and capable of understanding the meaning of life. Islamic Education teachers play a strategic role not only as instructors but also as facilitators, motivators, and counselors who guide students toward self-awareness, empathy, and moral resilience. This study aims to explore the role of Islamic Education teachers in fostering students’ spiritual and existential intelligence at State Elementary School 01 Medan City. Methodology: The research employed a qualitative case study approach with purposive site selection, as the school was considered active in guidance practices and open to character development. The main subjects were Islamic Education teachers and the principal. Data were collected through in-depth interviews, participatory observation, and documentation, and analyzed using Miles and Huberman’s interactive model of data reduction, display, and conclusion drawing. Data validity was ensured through source and method triangulation, persistence, and member checking. Main Findings: The results show that Islamic Education teachers play a significant role in instilling values of faith, empathy, and awareness of life’s meaning amidst the individualistic challenges of urban environments. Strategies include varied instructional methods, collaboration with parents, and institutional support, all of which strengthen their role in character development. Novelty/Originality of this study: This study highlights how Islamic Education teachers contribute uniquely to integrating spiritual and existential dimensions into education, offering a contextual model for holistic character formation in modern urban schools.